PERILAKU MEROKOK PADA REMAJA PUTRI DI KOTA MEDAN - Eka Cahyani; Irgi Ariyani; Nur Anisa; Putra Apriadi Siregar (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2025)
This study aims to understand the motivations and psychosocial dynamics behind smoking behavior in young women. Based on in-depth interviews with two informants—a university student and a barista—it was found that emotional stress, social pressure, and the need for relaxation were the primary factors driving their smoking habits. Despite having knowledge about the dangers of smoking, both informants exhibited a cognitive-behavioral gap due to emotional attachment and mild dependency. The study also revealed that permissive family attitudes and peer influence reinforced their behavior. Although both informants had attempted to quit, internal struggles and the lack of environmental support hindered their efforts. These findings highlight the need for a holistic approach—including psychological, social, and educational interventions—to support smoking cessation, especially among young women.